Formation and Development of Innovative Technologies in Livestock Farming - Jumanazarova M.E. F.R.Sattorov; Nortasheva M.A. (American Journal of Biodiversity, 2025)
In this article, meat and milk constitute the main share of products produced in this sector. Therefore, it is necessary to develop this sector with new innovative technologies and on a scientific basis, to improve the productivity, breeding, fertility, and technological characteristics of breeding cattle, especially pedigree cattle imported from foreign countries in recent years.